Consumer Ethnocentrism, National Identity, and Consumer Cosmopolitanism as Drivers of Consumer Behavior: A Social Identity Theory Perspective - Zeugner-Roth, Katharina Petra; Žabkar, Vesna; Diamantopoulos, Adamantios (IDEAS Working Paper Series from RePEc, 2015)
Consumers' preferences for domestic over imported products have been investigated in various isolated studies, but never in a single model incorporating several in-group and out-group consumer orientations at the same time. Building on social identity theory, this study develops and tests-in two countries-a conceptual model that assesses the relative influence of consumer ethnocentrism, national identity, and consumer cosmopolitanism on consumers' product judgments and willingness to buy domestic and foreign products. Furthermore, the study develops an empirically based typology of consumer segments using these sociopsychological traits and subsequently profiles them on consumption-relevant variables. The findings reveal several undiscovered patterns regarding the interplay of consumer ethnocentrism, national identity, and consumer cosmopolitanism as drivers of consumer behavior and offer managerial guidance on their relevance as segmentation variables.